(untitled) (REVISTA NODO, 2015)
The indivisibility between tangible and intangible cultural heritage has currently generated a debate that is reviewing the way that heritage issue has been working separately. In this article we take the categories of architectural heritage and tradition to endorse the debate on the integral treatment of cultural heritage, from the analysis of two particular cases: Tapalpa and San Sebastián del Oeste, in the State of Jalisco. Both localities recorded in the program of the Mexican Tourism Ministry, Pueblos Mágicos. As should cater to tourism activity and the way its development affects the relationship between architectural heritage, tradition and local people, in the processes of conservation and integral management of cultural heritage and its articulation with the social in search of affirming the identity of.